Expanding Who I Am: Validating the Self-Expansion Preference Scale. Issue 6 (1st November 2020) - Hughes, Erin K.; Slotter, Erica B.; Lewandowski, Gary W.
Abstract: People's self-concepts are subject to change through various processes, one of which is self-expansion. Self-expansion is a motivation to increase one's self-concept through engaging in novel, exciting, and interesting activities or by taking on one's partner's qualities. Despite the plethora of research on self-expansion, there has not been much work on whether people vary in their desire to expand. This study validates a new measure, called the Self-Expansion Preference Scale, to examine people's differing motivation for self-expansion. The sample included 611 participants who responded to 24 items, 12 of which pertained to self-expansion, a desire to increase the self-concept, and 12 of which pertained to self-conservation, a desire to maintain the self-concept. After reverse coding the 12 conserver items, an exploratory and confirmatory factor analysis indicated that there was a single dominant factor of self-expansion. The single-factor scale positively correlated with a series of both convergent measures (e.g., openness to experience) and predictive measures (e.g., hedonic well-being). Ultimately, the Self-Expansion Preference Scale offers new insight into a well-established process in an easily administered format. Looking forward, it would be interesting to see the implications of the scale as applied to romantic relationships, where self-expansion was initially researched.